2016
DOI: 10.1053/j.gastro.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Antibiotics to Children Before Age 2 Years Increases Risk for Childhood Obesity

Abstract: Background & Aims Childhood obesity is increasing and is associated with adult obesity. Antibiotics have been used to promote weight gain in livestock for several decades. Antibiotics are commonly prescribed for children, but it is not clear how exposure to antibiotics early in life affects risk for obesity. We performed a population-based cohort study to assess the association between antibiotic exposure before age 2 years and obesity at age 4 years. Methods We performed a retrospective cohort study of 21,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
177
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(198 citation statements)
references
References 50 publications
(47 reference statements)
12
177
0
9
Order By: Relevance
“…14 Administration of three or more courses of antibiotics before children reach an age of two years is associated with an increased risk of early childhood obesity. 16 In a cohort study, 6.4 % children were obese at four years of age and exposure to antibiotics was associated with an increased risk of obesity at four years. 16 The more antibiotic courses, the stronger the risk.…”
Section: Antibiotics and Weightmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Administration of three or more courses of antibiotics before children reach an age of two years is associated with an increased risk of early childhood obesity. 16 In a cohort study, 6.4 % children were obese at four years of age and exposure to antibiotics was associated with an increased risk of obesity at four years. 16 The more antibiotic courses, the stronger the risk.…”
Section: Antibiotics and Weightmentioning
confidence: 99%
“…16 In a cohort study, 6.4 % children were obese at four years of age and exposure to antibiotics was associated with an increased risk of obesity at four years. 16 The more antibiotic courses, the stronger the risk. 16 Children receiving antibiotics in the first year of life are more likely to be overweight at 12 years of age compared with those who were unexposed (32.4 vs 18.2%, P=0.002).…”
Section: Antibiotics and Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This learning has been extended to humans with a recent study suggesting that the administration of three or more courses of antibiotics before children reach an age of 2 years is associated with an increased risk of early childhood obesity. 5 These observations remain a compelling argument for a microbiome affected aetiology of obesity.…”
Section: Acknowledg Ementmentioning
confidence: 99%
“…They found that exposure to antibiotics in the first two years of life is associated with an increase in the risk of early childhood obesity. They suggested that repeated antibiotic use-three or more courses-is highly responsible for an increased risk of obesity risk (1).…”
mentioning
confidence: 99%